An approach to select between the plausible kinetic models of a heterogeneous catalytic process using intraparticle diffusion with external mass transfer resistance - O. O. Zhokh; P. E. Strizhak (Discover Applied Sciences)
Abstract The reaction rate is sometimes thoroughly described by several kinetic models simultaneously. In this case, the discrimination of the particular model may be challenging. Herein, we demonstrate that a change in the rate-limiting step of a reaction mechanism may result in a significant deviation of the effectiveness factor even if the kinetic rate equations provide nearly identical reaction rates. On this basis, the comparison of the experimental effectiveness factor and the effectiveness factor calculated theoretically using the corresponding rate equations may shed light on the true reaction mechanism. Since many industrial processes operate under internal and external mass transfer limitations, the effectiveness factor is obtained by accounting for pore diffusion resistance and diffusion resistance at the outer surface of a catalyst particle. Verification of the obtained formalism is performed using the kinetic constants for the commercially available process of the methanol dehydration to dimethyl ether over γ-alumina catalyst.